Strategi Inovasi Manajemen Mutu untuk Meningkatkan Daya Saing Perguruan Tinggi di Era Digital - Hendi Kurniyawan; Achmad Fais Ghozali (Educational Research Center, 2025)
This study aims to examine innovative quality management strategies to enhance the competitiveness of higher education institutions in the digital era. Using a qualitative case study approach, data were collected through in-depth interviews and observations in several university units that have implemented digitally based quality systems. The findings reveal that digital technologies such as quality dashboards, academic information systems, and automated reporting function effectively in supporting data-driven decision-making. However, the success of innovation strategy implementation largely depends on an adaptive and collaborative organizational structure with a strong quality culture. The study also highlights the importance of integrating technology, human resources, and internal regulations to create a sustainable quality system. The implications of this research suggest that digitalization of quality management must be accompanied by organizational capacity building so that innovation is not merely administrative, but can genuinely enhance institutional competitiveness